‘...but have you read this?’: dialogicity in Robert Thornton’s Holy name devotions - Lutton, Rob (Oxford University Press, 2018)
This article examines a particular set of texts in an early fifteenth-century religious anthology composed by the Yorkshire gentleman Robert Thornton. Together with other religious prose and verse, Thornton copied a number of Middle English and Latin texts, on the subject of devotion to the Holy Name of Jesus, into the folios of what is now Lincoln Cathedral MS 91. The article demonstrates the uniqueness of this set of Holy Name texts in late medieval England, both in terms of individual items and the combination of material. Some of these texts, namely those written by the English mystic Richard Rolle, were controversial in their treatment of the Name of Jesus, and contained claims for which some of Rolle’s followers were criticised by the early fifteenth century. I argue that their controversial content does not easily accord with scholarly characterisations of Thornton’s collecting impulses as conservative and spiritually unambitious. The article also discusses how Thornton copied other, more conservative, statements, that aimed to control Rollean Holy Name enthusiasm; in this case by that other great English mystical writer, Walter Hilton. I argue that this juxtapostion of enthusiastic and cautious statements points to practices of compilation and religious reading that were profoundly dialogic, bringing contradictory material together for use by Thornton’s household in their daily devotions that opened up a range of possible practices. Examination of the other religious texts within Lincoln MS 91 suggests some likely responses to the Holy Name material that Thornton copied. The article finishes with discussion of Thornton’s literary networks and how the diaologic nature of his literary practices would have involved complex social relationships with a range of clerical and lay agents. It asks how Thornton’s own agency might have worked in collaboration with clerical advisers who sought to guide, but did not control, his reading.